Edison Denisov The Russian Voice in European New Music. - Fanning, David 1955- (Oxford University Press, Oxford, 2004)
RESUMEN: By Yuri Kholopov and Valeria Tsenova; trans. by Romela Kohanovskaya. Studia Slavica Musicologica. Kuhn, Berlin, 2002